2001
DOI: 10.1007/s004410100425
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulfate proteoglycans in the rat thalamus: expression during postnatal development and correlation with calcium-binding proteins in adults

Abstract: Postnatal expression of chondroitin sulfate proteoglycans was studied in the rat thalamus by immunocytochemistry and Western immunoblotting techniques with monoclonal antibodies that recognize carbohydrate epitopes (clones CS-56, 1-B-5, 2-B-6). The complex of the results shows that these antibodies recognize mostly nonoverlapping molecules whose expression is regulated during postnatal development. Chondroitin sulfate proteoglycans, recognized by antibody CS-56, and hyaluronan, identified by antibody 1-B-5 aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Vitellaro-Zuccarello et al [ 88 ] and Seeger et al [ 86 ] found that the distribution of PNNs throughout the thalamus was very variable. This does not conflict with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Vitellaro-Zuccarello et al [ 88 ] and Seeger et al [ 86 ] found that the distribution of PNNs throughout the thalamus was very variable. This does not conflict with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In subjects with schizophrenia, we first reported marked decreases of CSPG-labeled PNNs in the amygdala and entorhinal cortex [ 42 ], interconnected brain regions involved in emotion-related learning and associative sensory information processing and in the pathophysiology of schizophrenia [ 43 47 ]. In this study, PNNs were detected using the lectin wisteria floribunda agglutinin (WFA; Figure 1 ), which labels PNNs predominantly associated with GABAergic neurons expressing the calcium binding protein parvalbumin (PVB) [ 48 54 ]. Consistently, lower numbers of WFA-labeled PNNs were observed in the lateral nucleus of the amygdala and the superficial layers of the entorhinal cortex, where these interneurons are primarily located [ 42 ].…”
Section: Schizophreniamentioning
confidence: 99%
“…This process occurs in an experience-driven manner, regulated by both excitatory glutamatergic inputs and inhibition mediated by GABA-A receptors, and coincides with the closure of critical developmental periods, and PVB-positive neurons maturation (Koppe et al, 1997, Vitellaro-Zuccarello et al, 2001, Pizzorusso et al, 2002, Dityatev and Schachner, 2003, Hensch, 2005, Dityatev and Schachner, 2006, Pizzorusso et al, 2006, Dityatev et al, 2007, Sugiyama et al, 2008, Balmer et al, 2009, Gogolla et al, 2009, Dityatev et al, 2010a). For instance, in the visual cortex maturation of PNNs around PVB-positive neurons is a key determinant for the establishment of ocular dominance, culminating in the closure of the critical period (Saghatelyan et al, 2001, Pizzorusso et al, 2002, Sugiyama et al, 2008).…”
Section: Ecm Functions Bear Direct Relevance To the Pathophysiologmentioning
confidence: 99%
“…A juvenile form of ECM present in late embryonic life and early postnatal life does not organize into PNNs and supports neurogenesis and gliogenesis, cell migration, axonal outgrowth, synaptogenesis and synaptic rearrangement (Bandtlow and Zimmermann, 2000, Vitellaro-Zuccarello et al, 2001, Carulli et al, 2007, Zimmermann and Dours-Zimmermann, 2008, Maeda, 2010). In contrast, adult ECM is, in general, non-permissive for axonal outgrowth and regeneration (Rhodes and Fawcett, 2004, Galtrey and Fawcett, 2007, Fawcett, 2009); PNN maturation occurs late in postnatal development (Carulli et al, 2006, Gundelfinger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%